Development of Micro, Small, and Medium Enterprises (MSMEs) as an Effort for Economic Recovery Post-COVID-19 Pandemic - Ago, Gordius; Mardiah, Ainil; Suarmanayasa, I Nengah; Anwar, Amelia (PT Inovasi Pratama Internasional, 2025)
The purpose of this study was to determine MSME development as an effort to recover the economy after the COVID-19 pandemic. The method used is a qualitative research method with a field research approach, and the research location is in Pamekasan Regency, East Java. The analysis was carried out by researchers using an interactive model from Miles Huberman that is related to the role of the Pamekasan Regency Government, especially the Pamekasan Regency Cooperative Service, in implementing MSME development policies after the COVID-19 pandemic. Data collection in this study was carried out through a literature review by collecting various articles and books related to MSMEs in Pamekasan Regency, interviews, and field documentation according to the research criteria. The results of this study showed that post-Covid 19 pandemic economic recovery efforts, especially in Pamekasan district, have been carried out by the Cooperative Service by providing guidance in the forms of support, enabling, protection, maintenance, strengthening, and maintenance through activities such as training, financial assistance, access to credit, people's businesses (KUR), and others.